PENGARUH DOSIS BIOCHAR SEKAM PADI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicum L.) PADA ALFISOL - Hidayati Karamina; Bambang Siswanto; Viktor Herkulanus Maringan (Universitas Islam Kadiri, 2022)
Tomatoes are currently one of the horticultural commodities that have high economic value and can be planted in all types of soil from sandy soil to loamy soil, but the ideal soil is sandy loam that is fertile, loose and contains lots of organic matter and is rich in nutrients. . Alfisol is a young soil type that contains a lot of easily weathered minerals, rich in nutrients, base saturation level, CEC, and high nutrient reserves. Rice husk biochar is able to improve soil and increase plant productivity and is able to increase nutrient availability for plants. The aim of the study was to determine the effect of rice husk biochar on the yield of tomato plants in Alfisol soil. This research was conducted from September to December 2020 at Screen House, Dau District, Malang Regency. The study was conducted using a completely randomized design (CRD) consisting of 9 treatments and 3 replications, namely the administration of biochar (B0: control); (B1: 5 t.ha̵¹); (B2: 10 t.ha̵¹); (B3:15 t.ha̵¹); (B4: 20 t.ha̵¹); (B5:25 t.ha̵¹); (B6: 30 t.ha̵¹); (B7:35 t.ha̵¹); (B8:40 t.ha̵¹). Observation parameters were observed. The observation parameters included plant height, number of leaves, number of branches, number of flowers, number of fruit, fruit weight per plant and fruit weight per ha. The results showed that the administration of biochar at a dose of 5 t.ha̵¹ (B1) had a significant effect on fruit weight of 9.06 t.ha-1 and the number of flowers by 23. Giving rice husk biochar 20 t.ha-1 gave the best results on the number of leaves. (20.92 strands), and rice husk biochar 15 t.ha-1 gave the best results on the number of branches (4.08 branches).